Granular Cell Tumor of Breast: Rare Tumor Masquerading as Malignancy - Hirachan, Suzita; Singh, Yogendra P; Jha, Anamika; Manandhar, Usha (Journal of Institute of Medicine Nepal, 2020)
Granular cell tumor (GCT) is a rare soft tissue tumor that arises from the Schwann cells of peripheral nerves. It was first postulated by Abrikossoff in 1926 as Myoblastoma. About 5-15% of these tumors occur in the breast and less than 1% has the potential to be malignant. Here we present a case of 41 years old premenopausal woman with Benign GCT of the right breast, having clinically malignant features. The clinical and radiological features of GCT are similar to malignant lump. However, histology showing presence of sheets of polygonal cells with abundant granular eosinophilic cytoplasm with round nuclei and granules with Periodic acid–Schiff (PAS) positive, diastase resistant and S-100 antigen positive are confirmatory. Treatment of Granular cell tumor is wide local excision. There is apparently no role of chemotherapy and radiotherapy. The presence of GCT in the breast is quite rare and clinically as well as radiologically it may mimic malignancy, however with histopathology and appropriate immunohistochemistry, proper diagnosis can be made.